Modified vinylidene fluoride polymer as well as preparation method and application thereof

By controlling the specific content in the acrylic monomer when preparing the vinylidene fluoride polymer, the problem of insufficient mechanical properties and thermal stability of the polymer in the electrode adhesive is solved, and better battery cycling performance is achieved.

CN119431644APending Publication Date: 2025-02-14WANHUA CHEM (YANTAI) BATTERY IND CO LTD +2

Patent Information

Application Number
CN202411569783.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when vinylidene fluoride polymer is applied to electrode adhesives, there are problems of insufficient mechanical properties and thermal stability, which affects its cycling performance in the battery.

Method used

By controlling the dimer mass content, acetic acid mass content and polymer inhibitor mass content in the acrylic monomer, a modified vinylidene fluoride polymer is prepared to improve its mechanical properties and thermal stability, and optimize its bonding as an electrode The application performance of the agent.

Benefits of technology

The modified vinylidene fluoride polymer significantly improves its mechanical properties and thermal stability, enhances its application performance as an electrode adhesive, and improves the cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120262370000151
    Figure BDA0005120262370000151
  • Figure BDA0005120262370000201
    Figure BDA0005120262370000201
Patent Text Reader

Abstract

The invention relates to a preparation technology of a vinylidene fluoride polymer, and provides a modified vinylidene fluoride polymer and a preparation method and application thereof, the modified vinylidene fluoride polymer prepared by the method can further improve the mechanical property of the obtained polymer and improve the application performance of the polymer as an electrode binder. According to the preparation method of the modified vinylidene fluoride polymer, the modified vinylidene fluoride polymer is prepared by reacting components of raw materials including vinylidene fluoride and acrylic acid; wherein the mass content of a dimer in the acrylic acid raw material is 0.1 to 1000 ppm, the mass content of acetic acid is 0.1 to 2000 ppm, and the mass content of a polymerization inhibitor is 50 to 200 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation technology of a vinylidene fluoride polymer, and in particular to a modified vinylidene fluoride polymer and a preparation method and application thereof. Background Art

[0002] The main special feature of polyvinylidene fluoride (PVDF) in the family of fluorine-containing polymer materials is that it has both CF bonds and CH bonds, of which the CF bonds provide structural stability, excellent mechanical properties, aging resistance, high and low temperature resistance, insulation, chemical resistance, light resistance and flame retardancy, and the CH bonds provide solubility, making it easy to process. Therefore, PVDF resin is particularly suitable for use in coatings and viscous glues, such as for the preparation of coatings, lithium battery separator coatings, photovoltaic backplane coatings, lithium battery positive electrode adhesives, etc.

[0003] Polyvinylidene fluoride is known in the art to be suitable as an adhesive for making electrodes (particularly positive electrodes), for making composite diaphragms, and / or for coating porous diaphragms for non-aqueous electrochemical devices such as batteries. Fluoropolymers are traditionally used for applications requiring special properties, such as low surface energy, high chemical resistance, aging resistance, and electrochemical stability. However, these favorable properties also make fluoropolymers difficult to handle and limit their applications. For example, the lack of polar functional groups on fluoropolymers makes it difficult to adhere to substrates, difficult to promote crosslinking, difficult to provide sites for subsequent chemical modification, difficult to be wetted by water, and difficult to improve hydrophilicity.

[0004] Therefore, it is necessary to copolymerize or graft modify the molecular chain segments of polyvinylidene fluoride so that the polar functional groups of the fluorine-containing polymer properties can be added to the molecular chain segments of the polymer in various ways to enhance the special properties of the fluorine-containing polymer, such as improving its adhesion to polar substrates such as metal and glass.

[0005] Patent CN101679563B discloses a method for preparing a linear semi-crystalline fluorine-containing polymer, which comprises copolymerizing vinylidene fluoride with 0.05-10% of a hydrophilic (meth) acrylic acid monomer (preferably acrylic acid or hydroxyethyl acrylate), and continuously feeding an aqueous solution of the (meth) acrylic acid copolymer monomer under a polymerization pressure greater than the VDF critical pressure of 4.43Mpa, so that the (meth) acrylic acid monomer copolymer monomer randomly distributed units in the fluorine-containing polymer eventually reach at least 40%. The bonding strength and thermal stability of the fluorine-containing polymer are significantly improved, and the fluorine-containing polymer is suitable for lithium-ion battery binders.

[0006] Patent CN 109075343 B discloses an adhesive composition, an electrode mixture, an electrode, and a non-aqueous electrolyte secondary battery, wherein the vinylidene fluoride copolymer composition comprises vinylidene fluoride and an acrylic acid monomer, wherein the acrylic acid monomer is at least one selected from acrylic acid and methacrylic acid, and the ratio (Mn2 / Mnl) of the number average molecular weight (Mn2) of the vinylidene fluoride copolymer composition after adsorption on alumina to the number average molecular weight (Mnl) of the vinylidene fluoride copolymer composition before adsorption on alumina is less than 2, and the melting point of the vinylidene fluoride copolymer composition is above 160°C. The prepared vinylidene fluoride copolymer has sufficient adhesiveness and realizes an adhesive composition with excellent dispersibility of a conductive aid.

[0007] Patent CN104497190B discloses a method for preparing a vinylidene fluoride polymer used as a binder for lithium-ion battery electrode materials. The method comprises the following steps: adding deionized water, a dispersant (sodium carboxymethyl cellulose), a pH adjuster (sodium pyrophosphate, sodium acid pyrophosphate), a chain transfer agent (diethyl carbonate), vinylidene fluoride, and a second monomer (acrylic monomer) into a polymerization reactor, heating the reactor to 32-52°C, a reaction pressure of 6.0-9.0 MPa, a rotation speed of 800-1600 r / min, adding an initiator (perfluoroacyl peroxide), and terminating the reaction after 4-8 hours to obtain a vinylidene fluoride polymer with a slurry concentration of 30-50% and a spray drying temperature of 80-130°C. The vinylidene fluoride polymer with ultrahigh molecular weight, fine particle size, high purity, and high high temperature resistance and colorability is obtained. The lithium-ion battery prepared with the polymer has the advantages of low binder dosage, high peel strength, high energy density, and high cycle capacity retention rate.

[0008] Patent CN 103282393 B discloses a hydrophilic vinylidene fluoride polymer, and relates to a method for manufacturing a grafted fluorinated polymer, the polymer comprising at least one grafted side chain containing one or more glycoside repeating units, the method comprising polymerizing vinylidene fluoride (VDF), optionally one or more additional fluorinated monomers, and optionally, one or more (meth) acrylic monomers in the presence of at least one polysaccharide derivative, the polysaccharide derivative having a dynamic viscosity of less than 15 mpaxs, as measured in an aqueous solution at a concentration of 2% by weight at 20° C. according to ASTM D445. The provided polymer exhibits excellent hydrophilic surface properties while maintaining other excellent properties of the vinylidene fluoride polymer, such as thermal stability and mechanical properties, and can be manufactured in an easy manner without involving subsequent grafting or blending or other chemical modifications.

[0009] In addition, many other patents also describe methods for improving the adhesion of vinylidene fluoride polymers. For example, patent US2020190239A1 uses acrylate monomers to copolymerize vinylidene fluoride, and through precise process control, there is no sudden heat generation that causes uncontrolled reaction temperatures exceeding the set point to obtain a vinylidene fluoride polymer further comprising repeating units derived from (meth) acrylic acid monomers, showing good thermal stability. Patent US5415958A discloses the copolymerization of vinylidene fluoride with unsaturated dibasic acid monoester polar monomers, introducing carbonyl groups into the PVDF skeleton to improve its adhesion to different substrates.

[0010] The above patents have achieved some positive results by using different processes and methods to copolymerize and modify vinylidene fluoride polymers with acrylic monomers. However, there is still some room for improvement in the copolymerization and modification of vinylidene fluoride polymers in the prior art. Summary of the invention

[0011] The present invention provides a modified vinylidene fluoride polymer, a preparation method and application thereof. The modified vinylidene fluoride polymer is prepared by the method of the present invention, which can further improve the mechanical properties of the obtained polymer and improve the application performance as an electrode binder.

[0012] To achieve the purpose, the present invention provides the following technical solutions:

[0013] The present invention provides a method for preparing a modified vinylidene fluoride polymer, wherein the modified vinylidene fluoride polymer is prepared by reacting components including vinylidene fluoride and acrylic acid raw materials;

[0014] The mass content of the dimer in the acrylic acid raw material is 0.1-1000 ppm, the mass content of acetic acid is 0.1-2000 ppm, and the mass content of the inhibitor is 50-200 ppm.

[0015] Preferably, the dimer mass content in the acrylic acid raw material is 90-1000 ppm, more preferably 90-700 ppm.

[0016] Preferably, the mass content of the acetic acid in the acrylic acid raw material is 350-2000 ppm, more preferably 350-1000 ppm.

[0017] Preferably, the mass content of the polymerization inhibitor in the acrylic acid raw material is 50-100 ppm;

[0018] In some embodiments, the polymerization inhibitor is selected from one or more of hydroquinone, phenothiazine, and p-hydroxyanisole.

[0019] Preferably, the purity of the acrylic acid raw material is ≥99.8%, preferably ≥99.9%, more preferably ≥99.95%;

[0020] In some embodiments, the amount of the acrylic acid raw material is 0.01-5 wt %, preferably 0.01-2 wt %, of the amount of the vinylidene fluoride.

[0021] Preferably, the modified vinylidene fluoride polymer has an intrinsic viscosity of 2.0-4.0 dL / g in an N,N-dimethylacetamide solution at 25°C.

[0022] In some embodiments, the components used to prepare the polymer optionally include other fluorine-containing monomers;

[0023] Preferably, the other fluorine-containing monomers are selected from one or more of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, 2,3,3,3-tetrafluoropropylene, hexafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, 3,3,3-trifluoro-1-propylene, 2-trifluoromethyl-3,3,3-trifluoropropylene, and fluorinated vinyl ethers; preferably, the fluorinated vinyl ether is one or more of perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoropropyl vinyl ether, and perfluorobutyl vinyl ether;

[0024] Preferably, the amount of the other fluorine-containing monomers is 0-10 wt %, preferably 0.1-10 wt %, more preferably 0.1-5 wt % of the amount of the vinylidene fluoride.

[0025] In some embodiments, the components used to prepare the polymer further include one or more of a polymerization stabilizer, an initiator, and optionally other auxiliary agents;

[0026] Preferably, the polymer stabilizer is selected from one or more of cellulose compounds, polyvinyl alcohol, polyethylene glycol, and polyacrylic acid. Preferably, the cellulose compound is selected from one or more of methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose. Preferably, the amount of the polymer stabilizer is 0.01-1.5wt% of the amount of the vinylidene fluoride.

[0027] Preferably, the initiator is an organic peroxide initiator, preferably one or more of diisopropyl peroxydicarbonate, diethyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-amyl peroxypivalate, dibenzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl permaleate, diisopropyl peroxide, isopropyl hydroperoxide, tert-butyl peroxyacetate, 2,2'-di(tert-butylperoxy)butane, tert-butyl peroxyisopropylbenzene, and tert-butyl peroxyisopropyl carbonate; preferably, the amount of the initiator is 0.01-2wt% of the amount of the vinylidene fluoride, more preferably 0.1-1wt%;

[0028] Preferably, the other auxiliary agents include a pH regulator and / or a chain transfer agent; preferably, the chain transfer agent is 0.01-1 wt% of the amount of vinylidene fluoride added; preferably, the pH regulator is added so that the reaction is carried out in the range of pH 4-8.

[0029] In some embodiments, the polymer is prepared by one or more processes selected from the group consisting of suspension polymerization, emulsion polymerization, and CO2 supercritical polymerization, preferably by suspension polymerization;

[0030] In some embodiments, the polymerization reaction temperature for preparing the polymer is 40-100° C. and the pressure is 3.0-15.0 MPa.

[0031] The present invention also provides a modified vinylidene fluoride polymer prepared by the preparation method described above.

[0032] The present invention also provides a use of the modified vinylidene fluoride polymer as described above in an electrode binder for a battery or in the preparation of an electrode binder composition for a battery; the battery is, for example, a non-aqueous electrolyte secondary battery;

[0033] Preferably, the adhesive composition comprises the modified vinylidene fluoride polymer, an electrode active material, a non-aqueous solvent and an optional conductive aid;

[0034] Further preferably, the adhesive composition includes, by weight, 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, of a modified vinylidene fluoride polymer, and 90 to 99.5 parts by weight, preferably 95 to 99 parts by weight, of an electrode active substance; the amount of the non-aqueous solvent is 4 to 100 times, more preferably 6 to 50 times, the mass of the modified vinylidene fluoride polymer; the amount of the conductive aid is 0.02 to 4 times, more preferably 0.1 to 2 times, the mass of the modified vinylidene fluoride polymer.

[0035] The technical solution provided by the present invention has the following beneficial effects:

[0036] The modified vinylidene fluoride polymer prepared by the preparation method of the present invention has excellent mechanical properties, thermal stability and other properties, and also has excellent product purity. The modified vinylidene fluoride polymer provided by the present invention is used in an electrode adhesive to improve the application effect of the electrode adhesive.

[0037] The present invention controls the dimer content, acetic acid content and inhibitor content in the acrylic acid monomer used to prepare the modified vinylidene fluoride polymer within the above ranges, which is beneficial to improving the reaction efficiency while taking into account the good application performance of the obtained polymer in electrode binders, such as improved mechanical properties, and is beneficial to improving the cycle performance of the battery. DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0040] The present invention provides a method for preparing a modified vinylidene fluoride polymer, wherein the modified vinylidene fluoride polymer is prepared by reacting components including vinylidene fluoride and acrylic acid raw materials;

[0041] Wherein, the mass content of dimer in the acrylic acid raw material is 0.1-1000ppm (for example, 0.1, 10, 50, 90, 200, 500, 700, 1000ppm, etc.), the mass content of acetic acid is 0.1-2000ppm (for example, 0.1, 10, 50, 90, 200, 350, 500, 700, 1000, 1500, 2000ppm, etc.), and the mass content of inhibitor is 50-200ppm (for example, 50, 90, 100, 150, 200ppm, etc.).

[0042] The modified vinylidene fluoride polymer prepared by the preparation method of the present invention has excellent mechanical properties, thermal stability and other properties, and also has excellent product purity. The modified vinylidene fluoride polymer provided by the present invention is used in an electrode adhesive to improve the application effect of the electrode adhesive.

[0043] After extensive research, the inventors found that the dimer content, acetic acid content and inhibitor content in the acrylic acid monomer raw material will affect the reaction efficiency of the copolymerization of acrylic acid and vinylidene fluoride, and affect the properties of the prepared modified vinylidene fluoride polymer, such as affecting mechanical properties, thermal stability, etc., and ultimately will affect the application performance of the obtained polymer as an electrode binder. The inventors found that controlling the dimer content, acetic acid content and inhibitor content in the acrylic acid monomer used to prepare the modified vinylidene fluoride polymer within the above range at the same time is conducive to improving the reaction efficiency, while taking into account the good application performance of the obtained polymer used in the electrode binder, such as having improved mechanical properties, and is conducive to improving the cycle performance of the battery.

[0044] As is known to all, the industrial production methods of acrylic acid mainly include acetylene carbonylation, 3-hydroxypropionitrile, ketene, acrylonitrile hydrolysis, high-pressure Raper, modified Raper, propylene oxidation, etc. Among them, the most commonly used is propylene gas phase oxidation, which uses propylene, air and water as raw materials, and produces acrylic acid through oxidation reaction under the action of catalyst. The process includes three steps: oxidation reaction, absorption and separation, wherein the oxidation reactor generally adopts a shell and tube type or tower type reactor, the reaction temperature is controlled at 140-180°C, and the pressure is controlled at 0.2-0.4MPa. The gas generated by the reaction is cooled and absorbed to obtain an acrylic acid aqueous solution, and then separated by distillation to obtain pure acrylic acid. However, in the process of producing acrylic acid, by-products and impurities such as acetic acid are inevitably produced. As one of the main impurities, acetic acid has a boiling point (118°C) and physical properties very close to acrylic acid (boiling point 142°C), making it difficult to remove. In addition, acrylic acid belongs to a vinyl monomer that is very easy to polymerize. It is easy to undergo polymerization reaction during its production, transportation, and storage, such as generating acrylic acid dimer, or generating large, insoluble, white flocculent or colloid with a relative molecular weight, which affects the product quality and polymerization reaction of acrylic acid and even causes serious safety accidents. Therefore, it is necessary to add a certain amount of polymerization inhibitor to acrylic acid to prevent or slow down the self-polymerization reaction of acrylic acid, and the preferred polymerization inhibitor of acrylic acid is hydroquinone, phenothiazine, or one or more of p-hydroxyanisole. The inventors have found that in the process of preparing the modified vinylidene fluoride polymer, the acetic acid content, dimer content (i.e., acrylic acid dimer content), and inhibitor content in the acrylic acid monomer have an important influence on the reaction and polymerization rate of acrylic acid and vinylidene fluoride, the quality of the vinylidene fluoride polymer product, and the application performance as an electrode binder. By controlling the dimer mass content in the acrylic acid raw material to 0.1-1000ppm, the acetic acid mass content to 0.1-2000ppm, and the inhibitor mass content to 50-200ppm, not only the polymerization efficiency can be improved, but also the mechanical properties of the obtained vinylidene fluoride polymer can be improved, and the application performance of the polymer when used as an electrode binder can be improved, which helps to improve the battery cycle performance.

[0045] Preferably, the mass content of the dimer in the acrylic acid raw material is 90-1000ppm, more preferably 90-700ppm; preferably, the mass content of the acetic acid in the acrylic acid raw material is 350-2000ppm, more preferably 350-1000ppm; on the one hand, it is beneficial to obtain a vinylidene fluoride polymer with excellent performance, and on the other hand, it is beneficial to control the production and refining costs of acrylic acid within a reasonable range.

[0046] In the present invention, the mass content of the polymerization inhibitor in the acrylic acid raw material is controlled to be 50-200ppm, preferably 50-100ppm; too much polymerization inhibitor content in acrylic acid will affect the polymerization reaction efficiency of acrylic acid and vinylidene fluoride, or prolong the induction period of the reaction; while too little polymerization inhibitor content in acrylic acid will cause the polymerization reaction to be initiated too quickly, resulting in an overly violent reaction, and will also have an adverse effect on the quality and performance of the resulting polymer product, and will also cause the dimer to be produced too quickly, affecting the product quality of acrylic acid, and even causing self-polymerization, resulting in greater safety risks. Controlling the polymerization inhibitor content in acrylic acid within the above range, and coordinating the control of the dimer content and the acetic acid content, not only can good polymerization efficiency be taken into account, but also the resulting polymer has better mechanical properties required as an electrode binder, and can improve the cycle performance of the battery.

[0047] In a more preferred embodiment, the mass content of dimer in the acrylic acid raw material is controlled to be 90-700ppm, the mass content of acetic acid is 350-1000ppm, and the mass content of inhibitor is 50-100ppm. Not only does it not need to make more stringent purification requirements for the acrylic acid raw material and avoid excessively high purification costs, but the modified vinylidene fluoride polymer prepared based on the acrylic acid raw material has a short reaction induction period and high reaction efficiency. At the same time, the obtained polymer not only has better bonding strength when used as an electrode adhesive, but also is conducive to obtaining better battery cycle performance.

[0048] In a preferred embodiment, the purity of the acrylic acid is ≥99.8%, preferably ≥99.9%, and more preferably ≥99.95%.

[0049] In some embodiments, the amount of the acrylic acid raw material is 0.01-5wt% of the amount of the vinylidene fluoride, such as 0.01, 0.5, 1, 1.5, 2wt%, etc., preferably 0.01-2wt%.

[0050] Preferably, the modified vinylidene fluoride polymer has an intrinsic viscosity of 2.0-4.0 dL / g in N,N-dimethylacetamide solution at 25°C. The inventors have found that the modified vinylidene fluoride polymer having the above intrinsic viscosity range has a relatively ideal molecular weight level, which helps to take into account good melt processing characteristics and solubility in polar solvents, while also taking into account good mechanical properties, structural stability, etc. If the intrinsic viscosity is too high or too low, there may be difficulties in melt processing and inability to completely dissolve in polar solvents, resulting in processing and use problems; at the same time, controlling the specific viscosity within the above range is conducive to further ensuring that the mechanical properties, structural stability, etc. meet the use requirements.

[0051] In some embodiments, the components used to prepare the polymer optionally include other fluorine-containing monomers; other fluorine-containing monomers are selected from, but not limited to, one or more of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, trifluorochloroethylene, 2,3,3,3-tetrafluoropropylene, hexafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, 3,3,3-trifluoro-1-propylene, 2-trifluoromethyl-3,3,3-trifluoropropylene, and fluorinated vinyl ethers; preferably, the fluorinated vinyl ether is one or more of perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoropropyl vinyl ether, and perfluorobutyl vinyl ether; preferably, the amount of the other fluorine-containing monomers is 0-10wt% of the amount of the vinylidene fluoride, preferably 0.1-10wt%, and more preferably 0.1-5wt%.

[0052] In some embodiments, the components used to prepare the polymer further include a polymerization stabilizer and / or an initiator, and optionally other auxiliary agents;

[0053] The addition of a polymerization stabilizer is beneficial to improving the dispersibility of vinylidene fluoride and other fluorine-containing comonomers and non-fluorine-containing comonomers in water. Preferably, the polymerization stabilizer is selected from one or more of cellulose compounds, polyvinyl alcohol, polyethylene glycol, and polyacrylic acid. More preferably, the cellulose compound is selected from one or more of methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose. Preferably, the amount of the polymerization stabilizer is 0.01-1.5wt% of the amount of the vinylidene fluoride.

[0054] Preferably, the initiator is an organic peroxide initiator, preferably one or more of diisopropyl peroxydicarbonate, diethyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-amyl peroxypivalate, dibenzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl permaleate, diisopropyl peroxide, isopropyl hydroperoxide, tert-butyl peroxyacetate, 2,2'-di(tert-butylperoxy)butane, tert-butyl peroxyisopropylbenzene, and tert-butyl peroxyisopropyl carbonate; preferably, the amount of the initiator is 0.01-2wt% of the amount of the vinylidene fluoride, more preferably 0.1-1wt%;

[0055] Preferably, the other auxiliary agents include pH regulators and / or chain transfer agents. Among them, the chain transfer agent is used for the purpose of adjusting the molecular weight of the obtained vinylidene fluoride polymer. The chain transfer agent can be appropriately selected from the known compounds that can be used to adjust the molecular weight of the fluorine-containing polymer, for example, selected from but not limited to oxygen-containing compounds, such as one or more of alcohols, carbonates, ketones, esters and ethers; halogenated hydrocarbons, such as one or more of chlorocarbons, hydrochlorocarbons, chlorofluorocarbons and hydrochlorofluorocarbons; alkanes, such as one or more of ethane and propane. Preferably, the chain transfer agent uses one or more of diethyl carbonate, ethyl acetate, and diethyl malonate, and its addition amount is preferably 0.01-1wt% of the amount of vinylidene fluoride added. The polymerization reaction mixture may optionally include a pH regulator to maintain a controlled pH throughout the polymerization reaction. Generally, the pH is preferably controlled in the range of about 4-8 to minimize the generation of undesirable colors in the product. The pH regulator may include one or more of an organic acid and its alkali metal salt, an inorganic acid and its alkali metal salt, and a preferred pH regulator includes one or more of a phosphate and an acetate. The phosphate may be one salt of phosphoric acid or a mixture of its multiple salts.

[0056] Specifically, the polymer can be prepared by one or more processes of suspension polymerization, emulsion polymerization, and CO2 supercritical polymerization, which are all common processes for preparing vinylidene fluoride polymers in the art, and can be carried out by the corresponding existing processes in the art, without any particular restrictions. Preferably, the polymer is prepared by a suspension polymerization process, specifically, the modified vinylidene fluoride polymer of the present invention is prepared by suspension polymerization in an aqueous solution. Preferably, the amount of vinylidene fluoride in the polymer is not less than 80wt%, so as to obtain a vinylidene fluoride polymer having excellent chemical resistance, weather resistance, and heat resistance.

[0057] Generally, the polymerization reactor needs to be deoxygenated during the empty reactor stage or after adding polymerization aids. This is usually done by performing multiple nitrogen replacements under negative pressure. The oxygen content is preferably controlled below 20 ppm, more preferably below 10 ppm.

[0058] As is known, in the polymerization system, an appropriate amount of water is added to form a suspension. Preferably, the amount of water added is such that the solid content of the vinylidene fluoride polymer dispersion obtained by polymerization is 20-50%, preferably 20-40%.

[0059] As an example, the specific steps of preparing the modified vinylidene fluoride polymer of the present invention by suspension polymerization method include:

[0060] (a) adding deionized water, a polymerization stabilizer and an optional chain transfer agent into a polymerization reactor, stirring and mixing the mixture evenly, and passing nitrogen to remove oxygen;

[0061] (b) adding an initiator, vinylidene fluoride, acrylic acid, and / or other fluorine-containing monomers into a polymerization reactor, heating and raising the temperature to start a polymerization reaction;

[0062] (c) continuing to add the remaining polymerization monomers and optional initiator and optional chain transfer agent as needed, keeping the polymerization temperature and polymerization pressure stable within the desired range;

[0063] (d) when the addition of the polymerization monomer is completed and the polymerization pressure is less than the set value, the polymerization reaction is completed to obtain a fluorine-containing polymer dispersion;

[0064] (e) Degassing, washing, filtering and drying are performed as required to obtain the desired modified vinylidene fluoride polymer.

[0065] In the present invention, the polymerization reactor used for the polymerization reaction can be a type of polymerization reactor known in the art, such as but not limited to a high-pressure spherical reactor, a high-pressure horizontal reactor, and a high-pressure vertical reactor. In some examples, the aspect ratio L / D of the polymerization reactor is less than 2, and more preferably L / D is less than 1.5, which is conducive to ensuring the heat transfer and mass transfer effect of the polymerization reaction. In addition, the stirring method in the polymerization reactor can be selected from one or more of a three-blade pitched propeller, a four-blade pitched propeller, an anchor propeller, a frame propeller, a screw belt propeller, etc.

[0066] Preferably, the polymerization reaction temperature for preparing the polymer is 40-100° C., and the pressure is 3.0-15.0 MPa.

[0067] The pressure in the polymerization reactor is raised to the polymerization initial temperature by the temperature in the reactor and fully exceeds the critical pressure (4.38MPa) of vinylidene fluoride. Vinylidene fluoride is mainly used for polymerization reaction in the state of supercritical fluid, and the pressure in the reaction system is generally reduced as the vinylidene fluoride monomer is used for polymerization, so it is generally necessary to continue to add vinylidene fluoride monomer to maintain the stability of the pressure in the polymerization reactor. If the pressure in the reactor when the above-mentioned reaction system is heated to the polymerization initial temperature is too high, a container with high pressure resistance is sometimes required, and if the pressure is too low, the polymerization reaction time is sometimes lengthened and the productivity is reduced. From the viewpoint of shortening the reaction time, the pressure in the reactor when the above-mentioned reaction system is heated to the polymerization initial temperature is preferably more than 3MPa, more preferably more than 4.4MPa. In addition, for example, from the viewpoint of reducing the cost of the polymerization reactor, the above-mentioned pressure is preferably less than 15MPa, more preferably less than 13MPa. The pressure can be adjusted according to various main factors such as the supply amount of vinylidene fluoride and comonomer, polymerization initial temperature, monomer density, etc.

[0068] At the same time, the polymerization initial temperature can be appropriately determined within a temperature range sufficient to make the vinylidene fluoride in the reactor a supercritical state. Within this range, if the polymerization initial temperature is too low, the reaction time of the suspension polymerization becomes longer, and thus, sometimes the productivity of the vinylidene fluoride polymer becomes lower, and if the polymerization initial temperature is too high, the pressure of the reaction system of the suspension polymerization increases, and sometimes a reactor with higher pressure resistance is required. From the viewpoint of improving the productivity of the vinylidene fluoride polymer, the polymerization initial temperature is preferably above 40°C, more preferably above 45°C. In addition, from the viewpoint of suppressing the pressure surge of the reaction system, the polymerization initial temperature is preferably below 100°C, more preferably below 70°C.

[0069] In the present invention, the endpoint control of the suspension polymerization is appropriately selected by considering the balance between the reduction of the amount of unreacted monomers and the extension of the polymerization time (i.e., the productivity of the product polymer). For example, the endpoint of the suspension polymerization can be determined by the temperature rise in the reaction system and the pressure change accompanying this in addition to sampling the reaction product.

[0070] In some examples, the modified vinylidene fluoride polymer is obtained in the form of a powder, which is obtained by dehydrating, washing and drying the polymer slurry after the suspension polymerization. According to the preparation process provided by the present invention, the reaction efficiency can be improved and the polymerization time can be shortened. Specifically, after the raw materials are supplied to the reactor, the polymerization time from the time point of reaching the initial polymerization temperature to the end of the polymerization is preferably within 20 hours, more preferably within 15 hours.

[0071] The present invention also provides a modified vinylidene fluoride polymer prepared by the preparation method described above.

[0072] The present invention also provides an application of a modified vinylidene fluoride polymer prepared by the preparation method as described above in an electrode binder for a battery, or in the preparation of an electrode binder composition for a battery, such as a positive electrode binder composition; the battery is, for example, a non-aqueous electrolyte secondary battery, and the modified vinylidene fluoride polymer provided by the present invention is particularly suitable for use in an electrode binder for a non-aqueous electrolyte secondary battery.

[0073] Preferably, the electrode binder composition comprises the modified vinylidene fluoride polymer, an electrode active material, a non-aqueous solvent and an optional conductive aid, etc.;

[0074] Further preferably, the electrode adhesive composition includes, by weight, 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, of a modified vinylidene fluoride polymer, and 90 to 99.5 parts by weight, preferably 95 to 99 parts by weight, of an electrode active substance; the amount of the non-aqueous solvent is 4 to 100 times, more preferably 6 to 50 times, of the mass of the modified vinylidene fluoride polymer; the amount of the conductive aid is 0.02 to 4 times, more preferably 0.1 to 2 times, of the mass of the modified vinylidene fluoride polymer.

[0075] An electrode for a non-aqueous electrolyte secondary battery can be obtained by coating the above-mentioned electrode adhesive composition on a metal current collector and drying it. The metal current collector is the substrate of the electrode and is a terminal for extracting electricity. The material of the metal current collector includes, for example, iron, stainless steel, steel, copper, aluminum, nickel and titanium. Aluminum foil is preferably used as the metal current collector. The thickness of the metal current collector is usually 5 to 100 μm, preferably 5 to 20 μm. As a coating method for the electrode adhesive composition, it can be selected from a wire rod coater, a blade coater, and a roller coater for coating. The electrode adhesive composition is coated on at least one side of the current collector, preferably on both sides. The drying temperature of the electrode adhesive composition is preferably 50 to 150 ° C, the drying time is preferably 30 to 300 minutes, and the pressure during drying is not particularly limited, usually under atmospheric pressure or under reduced pressure. In addition, after the electrode adhesive composition is dried, the composition can be pressed to increase the electrode energy density.

[0076] The electrode active material is not particularly limited, and known negative electrode active materials and positive electrode active materials can be used. As the negative electrode active material, it can be a carbon material, a silicon material, a metal / alloy material, a metal oxide, etc., wherein a carbon material is preferably used, including artificial graphite, natural graphite, difficult graphitized carbon, easy graphitized carbon, etc. A carbon material can be used alone or in combination of two or more. As the positive electrode active material, it is generally a lithium-based positive electrode active material containing lithium, such as lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and nickel-cobalt-manganese ternary materials.

[0077] The non-aqueous solvent is used to dissolve the modified vinylidene fluoride polymer, and can be selected from one or more of N-methyl-2-pyrrolidone, dimethylformamide, N,N-dimethylacetamide, N,N-dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate, acetone, methyl ethyl ketone and tetrahydrofuran, etc. The amount of the non-aqueous solvent is, for example, 4-100 times the mass of the modified vinylidene fluoride polymer, more preferably 6-50 times. Within this range, the solution viscosity of the electrode binder composition can be made moderate and easy to handle.

[0078] The conductive aid is mainly used to improve the electrochemical performance of the electrode binder composition. The conductive aid can be selected from carbon black, carbon nanotubes, graphite powder, graphite fiber and other carbonaceous materials, and metal powders or metal fibers such as nickel and aluminum. The amount of the conductive aid is, for example, 0.02-4 times the mass of the modified vinylidene fluoride polymer, more preferably 0.1-2 times.

[0079] The method for producing the electrode binder composition for a non-aqueous electrolyte secondary battery is not particularly limited, and the components may be mixed by a known method. The order of mixing the components is not particularly limited.

[0080] The present invention is further described below by way of examples, but it should not be understood that the present invention is limited thereto.

[0081] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0082] The main test methods involved in the following embodiments are as follows:

[0083] <1> Conductivity test

[0084] The aqueous solution of the vinylidene fluoride polymer after the polymerization reaction was completed was taken and its conductivity was tested using a Mettler Toledo S230K conductivity meter.

[0085] <2> Test of acrylic acid monomer content

[0086] The content of acrylic acid monomer in the prepared vinylidene fluoride polymer was determined by H spectral analysis using NMR (Bruker 600 MHz liquid nuclear magnetic resonance spectrometer).

[0087] <3> Intrinsic viscosity test

[0088] Weigh 0.02g of vinylidene fluoride polymer sample, accurate to 0.0001g, place in a 25mL volumetric flask, add 15-20mL N,N-dimethylacetamide, seal and shake, and place in a 120℃ forced air drying oven to dissolve for 4-6h. Visually observe that the sample is a clear and transparent liquid, which is considered to be completely dissolved. Then move the volumetric flask to a constant temperature water bath at 25℃±0.2℃, add N,N-dimethylacetamide at a constant temperature of 25℃ to the scale, and shake well. The viscometer is an Ubbelohde viscometer with an inner diameter of 0.56-0.60mm. Calculation of test results:

[0089] The intrinsic viscosity is expressed as [η] and the result is calculated as follows:

[0090]

[0091] Where:

[0092] [η]—intrinsic viscosity, unit: dL / g; t—time for the solution of the substance being measured to flow through the viscometer, unit: s; t0—time for the pure solvent to flow through the viscometer, unit: s; m—mass of the substance being measured, unit: g; 0.25—dissolved volume of the substance being measured, unit: dL.

[0093] <4> Preparation of electrodes for non-aqueous electrolyte secondary batteries

[0094] 5g of the prepared vinylidene fluoride polymer was added to 100g of N-methylpyrrolidone and stirred until the fluorine-containing polymer was completely dissolved. Then 3.75g of ultrafine carbon powder Super P and 1.25g of carbon nanotubes were added to the solution and mixed evenly using a mechanical stirrer. Then 240g of electrode active material (nickel-cobalt-manganese ternary material LiNi x Co y Mn z O2, wherein x+y+z=1), mixed, degassed, and allowed to stand to obtain a paste-like secondary battery electrode binder composition having a viscosity and fineness that meet the requirements (viscosity between 4000-8000cp, fineness ≤20 microns), with no oil stains, bubbles, or suspended particles on the appearance. The obtained secondary battery electrode binder composition is then evenly coated on an aluminum foil with a coating machine at a wet thickness of 350 μm, heated in a vacuum oven at 120°C for 150 minutes, and then compacted with a roller press to obtain a non-aqueous electrolyte secondary battery electrode containing a coating.

[0095] <5> Bond strength test

[0096] Will <4> The electrode for the non-aqueous electrolyte secondary battery prepared in the method is cut into a strip electrode piece of 20 cm × 2.5 cm, and the strip electrode piece is bonded to a rigid aluminum plate using a double-sided adhesive (the double-sided adhesive is applied to the side of the strip electrode piece containing the coating). A GOTECH model AI-7000-LA tensile testing machine is used to fix the rigid aluminum plate at one end and the other end on the strip electrode piece for peeling test. The test standard is the ISO 4624 adhesion pull-off test, the peeling angle is 180°, and the displacement rate of the clamp is set to 100 mm / min to determine the peel strength between the electrode adhesive composition for non-aqueous electrolyte secondary batteries and the metal current collector (aluminum foil).

[0097] <6> Battery cycle performance test

[0098] In an argon atmosphere glove box that meets environmental standards (water content <1ppm, oxygen content <1ppm), 30 parts by mass of ethylene carbonate, 20 parts by mass of diethyl carbonate, and 45 parts by mass of ethyl methyl carbonate are mixed evenly, and then 5.0 parts by mass of lithium hexafluorophosphate are added thereto to prepare an electrolyte; the diaphragm adopts a polyethylene base film with a thickness of 12μm + a ceramic coating with a thickness of 4μm; the electrodes for the non-aqueous electrolyte secondary battery prepared above (as a positive electrode), an electrolyte, a diaphragm, and a lithium sheet are assembled to obtain a simulated lithium-ion battery (half-cell). The prepared lithium-ion battery was subjected to a cycle performance test at a current density of 0.5C using an electrochemical workstation. The capacity retention rate of the battery after 100 cycles is calculated using the following formula:

[0099] Capacity retention rate after 100 cycles (%) = discharge capacity after 100th cycle / discharge capacity after first cycle.

[0100] <7> Determination of acrylic acid dimer, inhibitor and acetic acid content in acrylic acid raw materials

[0101] First, take about 1 mL of acrylic acid raw material sample, add 10 mL of methanol, and shake at room temperature for 5 minutes to fully dissolve it; then take 1 mL of the solution, use a pipette to suck it into the sample bottle of the gas chromatograph (Shimadzu GCMS-QP 2020), add 1 mL of diclofenac internal standard solution (100 μg / mL methanol solution), and mix it thoroughly. Put the sample bottle into the gas chromatograph for testing. Through the detection and calculation of the gas chromatograph, the content and purity of each component in acrylic acid can be obtained.

[0102] The raw materials information required for the experiment is as follows:

[0103] Hydroxypropyl methylcellulose: HPMC, Shandong Heda Chemical, product brand HEADCEL 75HD100;

[0104] Tert-butyl peroxypivalate: TBPP, Hubei Kanosi Technology Co., Ltd.;

[0105] Acrylic acid raw material a: AA, Wanhua Chemical, product purity ≥99%, p-hydroxyanisole mass content ≤200ppm.

[0106] The test methods in the embodiments and comparative examples are as follows:

[0107] Prefabrication Example 1 (Acrylic Acid Raw Material D1)

[0108] Inject acrylic acid raw material a and hydrazine hydrate (N2H4 mass fraction of 75%) into acrylic acid purification unit at a mass ratio of 2000:1 and mix them evenly at 25-30°C. During the mixing process, impurities such as aldehydes and ketones in acrylic acid raw material a react with hydrazine hydrate; all the obtained mixed materials are passed into the distillation unit, and the reactants first enter the distillation tower with a temperature of 60-65°C and a tower top pressure of 3.0-4.5KPa for distillation, and condense the gaseous materials produced by the distillation tower at a condensation temperature of 21-24°C to obtain the first condensate; at the same time, send the liquid materials produced by the distillation tower to the recovery tower, and The temperature of the bottom of the tower is maintained at 60-65° C., the gas phase produced in the recovery tower is extracted and condensed at 21-24° C. to obtain a second condensate; the first condensate and the second condensate are both introduced into a falling film crystallization purification unit for falling film crystallization at a temperature of -23--17° C., and the uncrystallized liquid phase enters a condensation sweating heat unit for sweating cooling, and the sweating temperature is 14-17° C. The sweated material and the crystallized material are combined to form a high-purity acrylic acid raw material D1, wherein the mass content of p-hydroxyanisole is 5 ppm, the mass content of acrylic acid dimer is 97 ppm, the mass content of acetic acid is 384 ppm, and the purity of acrylic acid is 99.95%.

[0109] Prefabrication Example 2 (Acrylic Acid Raw Material A1)

[0110] A small amount of p-hydroxyanisole was added to the high-purity acrylic acid raw material D1 obtained in Preparative Example 1 so that the mass content of p-hydroxyanisole was 55 ppm, thereby obtaining acrylic acid raw material A1, wherein the purity of acrylic acid was 99.94%.

[0111] Example 1

[0112] The acrylic acid raw material used in this example is the acrylic acid raw material A1 obtained in Preparative Example 2, which is prepared into an acrylic acid aqueous solution with a mass concentration of 1.2%.

[0113] At room temperature, 3350g of deionized water and 2.4g of hydroxypropyl methylcellulose were added to a high-pressure polymerization kettle with an effective volume of 8 liters, and the stirring was turned on to a speed of 600rpm to mix the bottom liquid of the kettle evenly. Under vacuum conditions, nitrogen was passed through for multiple times to replace oxygen (oxygen content <20ppm), and then 7.2g of tert-butyl peroxypivalate, 85g of acrylic acid aqueous solution, and 2100g of 1,1-vinylidene fluoride were added. The temperature was raised to 50°C (initial reaction temperature) and the pressure was 10.0Mpa (initial reaction pressure). The polymerization reaction started, and the temperature was lowered by circulating water. After the reaction temperature stabilized, 1630g of acrylic acid aqueous solution was continuously added to maintain the reaction pressure at 10.0Mpa. After the addition of the polymerization monomer was completed, the reaction temperature was maintained at 50°C. When the reaction pressure dropped to 5.0Mpa, the polymerization reaction was completed, and then the obtained polymer dispersion was degassed, washed with water, filtered, and then dried at 80°C for 12 hours to obtain vinylidene fluoride polymer resin powder.

[0114] Example 2

[0115] The same method was used as in Example 1, except that the acrylic acid used was acrylic acid raw material A2, which was prepared by adding a small amount of p-hydroxyanisole to the acrylic acid raw material A1 prepared in Preparative Example 2, so that the mass content of p-hydroxyanisole in the raw material reached 95 ppm, and the purity of the acrylic acid raw material was 99.94%.

[0116] Example 3

[0117] The same method was used as in Example 1, except that the acrylic acid used was acrylic acid raw material A3, which was prepared by adding a small amount of p-hydroxyanisole to the acrylic acid raw material A1 prepared in Preparative Example 2, so that the mass content of p-hydroxyanisole in the raw material reached 155 ppm, and the purity of the acrylic acid raw material was 99.93%.

[0118] Example 4

[0119] The same method is used as in Example 1, except that the acrylic acid used is acrylic acid raw material A4, which is obtained by storing acrylic acid raw material A1 prepared in Preparative Example 2, and the acrylic acid dimer content is 500 ppm and the acrylic acid purity is 99.91%.

[0120] Example 5

[0121] The same method was used as in Example 1, except that the acrylic acid used was acrylic acid raw material A5, which was obtained by storing acrylic acid raw material A1 prepared in Preparative Example 2, and the acrylic acid dimer content was 900 ppm and the acrylic acid purity was 99.87%.

[0122] Example 6

[0123] The same method was used as in Example 1, except that the acrylic acid used was acrylic acid raw material A6, which was obtained by adding a small amount of acetic acid to acrylic acid raw material A1 prepared in Preparative Example 2. The acetic acid content of the raw material was 884 ppm, and the acrylic acid purity was 99.9%.

[0124] Example 7

[0125] The same method was used as in Example 1, except that the acrylic acid used was acrylic acid raw material A7, which was obtained by adding a small amount of acetic acid to acrylic acid raw material A1 prepared in Preparative Example 2. The mass content of acetic acid in the raw material was 1884 ppm, and the purity of acrylic acid was 99.8%.

[0126] Comparative Example 1

[0127] Carry out with reference to Example 1, except that: the acrylic acid raw material used is replaced by industrial acrylic acid (acrylic acid raw material D2), the product purity of this raw material is 99.2%, wherein the p-hydroxyanisole mass content is 185ppm, the acrylic acid dimer mass content is 2600ppm, and the acetic acid mass content is 3530ppm.

[0128] Comparative Example 2

[0129] The same method was used as in Example 1, except that the acrylic acid raw material used was acrylic acid raw material D3, which was prepared by adding a small amount of p-hydroxyanisole to acrylic acid raw material A1 prepared in Preparative Example 2, wherein the p-hydroxyanisole content was 305 ppm and the acrylic acid purity was 99.92%.

[0130] Comparative Example 3

[0131] The same method is used as in Example 1, except that the acrylic acid raw material used is acrylic acid raw material D4, which is obtained by storing acrylic acid raw material A1 prepared in Preparative Example 2, and the acrylic acid dimer content in the raw material is 2000 ppm, and the acrylic acid purity is 99.75%.

[0132] Comparative Example 4

[0133] The same method was used as in Example 1, except that the acrylic acid raw material used was acrylic acid raw material D5, which was obtained by adding a small amount of acetic acid to acrylic acid raw material A1 prepared in Preparative Example 2, and the acetic acid content in the raw material was 2800 ppm, and the acrylic acid purity was 99.7%.

[0134] Comparative Example 5

[0135] The process is carried out in accordance with Example 1, except that the acrylic acid raw material is replaced by the acrylic acid raw material D1 prepared in Preparative Example 1.

[0136] The vinylidene fluoride polymer resins prepared in each embodiment and comparative example were tested according to the method described above, and electrodes for non-aqueous electrolyte secondary batteries were prepared respectively, and the bonding strength between the electrode binder composition and the metal current collector (aluminum foil) was tested, and lithium ion batteries were prepared and the battery cycle performance was tested. The test results are shown in Table 1:

[0137] Table 1. Performance test results

[0138]

[0139] In Table 1, "reaction induction period" refers to the time from when the temperature of the polymerization kettle reaches the required initial reaction temperature and the pressure reaches the initial reaction pressure to when the polymerization reaction starts to start; the judgment criterion for the start of the polymerization reaction is: the time when the reaction temperature starts to rise on the basis of the initial reaction temperature, and the reaction pressure starts to decrease on the basis of the initial reaction pressure.

[0140] It can be seen from the above test results that the performance of the vinylidene fluoride polymer prepared in the embodiment is significantly better than that of the comparative example. The present invention can take into account high reaction efficiency and a relatively short reaction induction period by controlling the content of the inhibitor, dimer and acetic acid in the acrylic acid monomer used to prepare the vinylidene fluoride polymer. At the same time, the prepared vinylidene fluoride polymer has better application performance when used in electrode adhesives. Using the polymer obtained in the embodiment of the present invention as an electrode adhesive for non-aqueous electrolyte secondary batteries can improve the bonding strength between the electrode adhesive composition for non-aqueous electrolyte secondary batteries and the metal current collector (aluminum foil), thereby improving the electrochemical properties and service life of the electrodes for non-aqueous electrolyte secondary batteries, and having a better cycle capacity retention rate.

[0141] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A method for preparing a modified vinylidene fluoride polymer, comprising reacting components including vinylidene fluoride and acrylic acid raw materials to prepare the modified vinylidene fluoride polymer; characterized in that: The mass content of dimer in the acrylic acid raw material is 0.1-1000 ppm, the mass content of acetic acid is 0.1-2000 ppm, and the mass content of polymerization inhibitor is 50-200 ppm.

2. The preparation method according to claim 1, characterized in that: The dimer mass content in the acrylic acid raw material is 90-1000 ppm, more preferably 90-700 ppm.

3. The preparation method according to claim 1 or 2, characterized in that: The mass content of the acetic acid in the acrylic acid raw material is 350-2000 ppm, more preferably 350-1000 ppm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mass content of the polymerization inhibitor in the acrylic acid raw material is 50-100 ppm; And / or, the polymerization inhibitor is selected from one or more of hydroquinone, phenothiazine, and p-hydroxyanisole.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The purity of the acrylic acid raw material is ≥99.8%, preferably ≥99.9%, more preferably ≥99.95%; And / or, the amount of the acrylic acid raw material is 0.01-5wt% of the amount of the vinylidene fluoride, preferably 0.01-2wt%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The modified vinylidene fluoride polymer has an intrinsic viscosity of 2.0-4.0 dL / g in an N,N-dimethylacetamide solution at 25°C.

7. The preparation method according to any one of claims 1 to 5, characterized in that: The components used to prepare the polymer also include a polymerization stabilizer and / or an initiator, and optionally include one or more of other fluorine-containing monomers and other auxiliary agents; Preferably, the other fluorine-containing monomers are selected from one or more of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, 2,3,3,3-tetrafluoropropylene, hexafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, 3,3,3-trifluoro-1-propylene, 2-trifluoromethyl-3,3,3-trifluoropropylene, and fluorinated vinyl ethers; preferably, the fluorinated vinyl ether is one or more of perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoropropyl vinyl ether, and perfluorobutyl vinyl ether; Preferably, the amount of the other fluorine-containing monomers is 0-10 wt %, preferably 0.1-10 wt %, more preferably 0.1-5 wt % of the amount of the vinylidene fluoride. Preferably, the polymer stabilizer is selected from one or more of cellulose compounds, polyvinyl alcohol, polyethylene glycol, and polyacrylic acid. Preferably, the cellulose compound is selected from one or more of methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose. Preferably, the amount of the polymer stabilizer is 0.01-1.5wt% of the amount of the vinylidene fluoride. Preferably, the initiator is an organic peroxide initiator, preferably one or more of diisopropyl peroxydicarbonate, diethyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, tert-amyl peroxypivalate, dibenzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl permaleate, diisopropyl peroxide, isopropyl hydroperoxide, tert-butyl peroxyacetate, 2,2'-di(tert-butylperoxy)butane, tert-butyl peroxyisopropylbenzene, and tert-butyl peroxyisopropyl carbonate; preferably, the amount of the initiator is 0.01-2wt% of the amount of the vinylidene fluoride, more preferably 0.1-1wt%; Preferably, the other auxiliary agents include a pH regulator and / or a chain transfer agent; preferably, the chain transfer agent is 0.01-1 wt% of the amount of vinylidene fluoride added; preferably, the pH regulator is added so that the reaction is carried out in the range of pH 4-8.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The polymer is prepared by one or more processes of suspension polymerization, emulsion polymerization, and CO2 supercritical polymerization, preferably by suspension polymerization; And / or, the polymerization reaction temperature for preparing the polymer is 40-100° C. and the pressure is 3.0-15.0 MPa.

9. A modified vinylidene fluoride polymer prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the modified vinylidene fluoride polymer according to claim 9 in an electrode binder for a battery or in the preparation of an electrode binder composition for a battery; the battery is, for example, a non-aqueous electrolyte secondary battery; Preferably, the adhesive composition comprises the modified vinylidene fluoride polymer, an electrode active material, a non-aqueous solvent and an optional conductive aid; Further preferably, the adhesive composition includes, by weight, 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, of a modified vinylidene fluoride polymer, and 90 to 99.5 parts by weight, preferably 95 to 99 parts by weight, of an electrode active substance; the amount of the non-aqueous solvent is 4 to 100 times, more preferably 6 to 50 times, the mass of the modified vinylidene fluoride polymer; the amount of the conductive aid is 0.02 to 4 times, more preferably 0.1 to 2 times, the mass of the modified vinylidene fluoride polymer.

Citation Information

Patent Citations

  • Vinylidene fluoride copolymers

    CN101679563B

  • hydrophilic vinylidene fluoride polymer

    CN103282393B

  • A method for preparing a vinylidene fluoride polymer for use as a binder in lithium-ion battery electrode materials.

    CN104497190B

  • Adhesive compositions, electrode mixtures, electrodes, and non-aqueous electrolyte secondary batteries

    CN109075343B

  • Vinylidene fluoride polymer

    US20200190239A1

Cited By

  • Lightweight high-strength self-compacting concrete and preparation method thereof

    CN122145112A